Pengaruh Pendapatan Pembiayaan Mudharabah terhadap Profitabilitas (ROA) pada PT. Bank Muamalat Indonesia Tbk. Periode 2011-2015 - Indah Wahyuningsih (IAIN Manado, 2018)
This research is about the influence of financing mudharabahincome of the result of profitability (return on assets) at PT. Bank Muamalat Indonesia Tbk. for period 2011 until 2015. The main problem in this research is how much financing mudharabahincome that calculated by ratio of mudharabahwhich is ratio of mudharabahincome and total revenue sharing income, influencing the profitability that calculated by return on assets (ROA) which is ratio of net income and total assets. This research has a purpose to describe and explain the influence between financing mudharabahincome with profitability (return on assets) at PT. Bank Muamalat Indonesia Tbk. for period 2011 until 2015. Research methods used in this research is quantitative descriptive analysis. The data used in this research is secondary data, in the form of financial statement of PT. Bank Muamalat Indonesia Tbk. as the population and the samples consist of quarter financial statement of PT. Bank Muamalat Indonesia that published from 2011 until 2015. The statistic method used to test the research hypothesis is simple regression. After following the quantitative procedural, the result of this research show that financial mudharabahincome has influence the profitability, which is proved with the significant value is 0,009 that smaller than 0.05. It means that financial musharabahincome has influence the profitability. Keyword : Mudharabah, Profitability, Return on Assets (ROA)